Street(e)scape: A Site-Specific and Contextual Approach in Documentation, Design Interventions, Cultural Mapping and Conservation of Sta. Catalina, Carcar, Cebu - Mata, Rene Luis S.; Cuaresma, Dani Josef C.; Cusi, Edgar Nonato G.; Dy, Gerard Michael D.; Feliciano, Mary Ann R.; Francisco, Frances Joy S.; Lustre, Crisanto III B.; Montero, Claudia Isabelle V.; Portem, Jayson B.; Singson, Manuel Agustin Z.; Tablante, Ivy Sychelle B.; Vitug, Marianne Claire V. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 4, 2013)
-